2008
DOI: 10.1109/tap.2008.919183
|View full text |Cite
|
Sign up to set email alerts
|

On the Diffusion of Electromagnetic Waves and Applicability of Diffusion Equation to Multipath Random Media

Abstract: The diffusion behavior of electromagnetic (EM) waves in two dimensional (2-D) multipath media is studied through integral equation based full wave Monte Carlo simulations. The influences of some physical factors are explored, among which the area density of the embedded obstacles manifests itself to be the most important one in determining wave diffusion. A lossy system starts to behave diffusively when the area density approximately exceeds 5%, and the diffusion equations are generally applicable for predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It can be seen that the mean error and standard deviation for the fully GO/UTD/DE approach and the novel technique GO/DE increase significantly in this third scenario. Thus, it is shown that DE approach does not work in this scenario, with planes with obstacles densities smaller than 10%, as it is shown in [43]. It can be concluded that it is highly important to achieve a tradeoff between precision of the results and simulation computational time, when these hybrid approaches are employed.…”
Section: Measurement Results and Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…It can be seen that the mean error and standard deviation for the fully GO/UTD/DE approach and the novel technique GO/DE increase significantly in this third scenario. Thus, it is shown that DE approach does not work in this scenario, with planes with obstacles densities smaller than 10%, as it is shown in [43]. It can be concluded that it is highly important to achieve a tradeoff between precision of the results and simulation computational time, when these hybrid approaches are employed.…”
Section: Measurement Results and Discussionmentioning
confidence: 83%
“…Following the approach described in [11,25,43], it has been developed a new module to be implemented in the 3D RL tool. This new module is based on DE and considers absorption and scattering losses caused by obstacles.…”
Section: A Ray Launching Modeling With Diffusion Equationmentioning
confidence: 99%
See 2 more Smart Citations